Obstructive Sleep Apnea in Patients with Heart Failure and Atrial Fibrillation - Anggia Chairuddin Lubis; Yuke Sarastri; Cut Aryfa Andra; Nadiah Masyab; Hana Fauziyah (Talenta Publisher, 2025)
Background: Obstructive sleep apnea (OSA) is an independent risk factor for heart failure and atrial fibrillation. Therefore, effective detection and management of OSA are essential. Objective: The study aimed to determine how common obstructive sleep apnea is among patients with heart failure and atrial fibrillation. Methods: We performed a cross-sectional study assessing the prevalence of OSA in hospitalized patients with both conditions, following the latest European Society of Cardiology Guidelines for heart failure assessment and using polysomnography to evaluate OSA. Results: The study included 30 subjects; 22 (73.3%) were men, and 18 (60%) were over 60 years old. Polysomnography revealed that 23 (80.0%) had OSA, with 4 (23.5%) in the severe category and an average AHI of 18.3 ± 14.7. Among participants, 11 (65%) with ejection fraction ≤ 40%, 12 (40%) had obesity, 11 (36.7%) had Type 2 diabetes, 19 (63.6%) had hypertension, 20 (66.7%) had coronary artery disease, and 3 (10%) had a history of stroke. Most participants (60%) had a history of smoking. Conclusion: This study shows a high prevalence of OSA among patients with heart failure and atrial fibrillation, especially in men and those with reduced ejection fraction.